2018
DOI: 10.1021/acsnano.8b00036
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Toxicity Produced by Mixtures of Biocompatible Gold Nanoparticles and Widely Used Surfactants

Abstract: Nanoparticle safety is usually determined using solutions of individual particles that are free of additives. However, the size-dependent properties of nanoparticles can be readily altered through interactions with other components in a mixture. In applications, nanoparticles are commonly combined with surfactants or other additives to increase dispersion or to enhance product performance. Surfactants might also influence the biological activity of nanoparticles; however, little is known about such effects. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…On repeating the assay in the absence of E. coli , the authors observed a reduced toxicity effect, illustrating unforeseen artifacts that could occur in such widely used toxicity assays. Ginzburg et al showed a synergistic toxicity effect induced by gold nanoparticles in the presence of additives such as surfactants, while the individual components separately exhibited low toxicity [ 80 ], underlining the importance of identifying strategies for selecting safe nanoparticles-additive/ligand/modifier combinations. Gold nanoparticles were also shown to have species-specific differences with respect to biodistribution, pathophysiologic response, and retention time.…”
Section: Current Limitationsmentioning
confidence: 99%
“…On repeating the assay in the absence of E. coli , the authors observed a reduced toxicity effect, illustrating unforeseen artifacts that could occur in such widely used toxicity assays. Ginzburg et al showed a synergistic toxicity effect induced by gold nanoparticles in the presence of additives such as surfactants, while the individual components separately exhibited low toxicity [ 80 ], underlining the importance of identifying strategies for selecting safe nanoparticles-additive/ligand/modifier combinations. Gold nanoparticles were also shown to have species-specific differences with respect to biodistribution, pathophysiologic response, and retention time.…”
Section: Current Limitationsmentioning
confidence: 99%
“…[172] For instance, surfactants (i.e., polysorbate 20, polysorbate 80, and SDS) exhibited synergistic toxicity with Au NPs in embryonic D. rerio, probably due to the increased bioavailability of surfactants by transport and internalization of the Au NPs. [173] Similarly, GO NSs coated with biological secretions in D. rerio culture water (e.g., small organic molecules, proteins, nucleotides, and mucopolysaccharides), induced more serious embryotoxicity in D. rerio with higher proportions of mortality and malformation. [97] In addition, tail flexure, pericardial edema, and faster heartbeat were observed in GO NS-treated juvenile fish.…”
Section: (10 Of 23)mentioning
confidence: 99%
“…Other research with peptide-capped Au NPs showed that the terminal modification was important, with the presence of terminal histidines being more toxic than tryptophans, with methionine conferring the least toxicity [ 92 ]. In addition, co-incubation of zebrafish embryos with Au NPs and a surfactant (polysorbate 20) resulted in increased uptake and toxicity [ 93 ]. Together this suggests that the overall shape and surface chemistry of the Au NPs are key determinants of biocompatibility.…”
Section: Selected Nanotoxicology Studies In Zebrafishmentioning
confidence: 99%